Management of an Intruded Ankylosed Immature Permanent Maxillary Central Incisor: A Case Report and Review of the Literature - Shekarchi, Fatemeh; kamareh, sanaz; Yadegari, Atiye; yaghoutiazar, sahar (Journal of Dental School, 2023)
Objectives Intrusive luxation is a severe type of dentoalveolar injury, which causes damage to the pulp and supporting tissues of a tooth, as the tooth is apically dislocated into the alveolar process. Case This report describes a case of re-eruption of an intruded immature severely ankylosed upper permanent central incisor. A seven-year-old boy was referred to the pediatric dental clinic three months after a traumatic injury. Clinical and radiographic examinations revealed intrusive luxation of the immature left upper permanent central incisor. In the first visit, initial bracketing was performed, and the left central incisor was engaged. In the second visit (after four weeks), the tooth showed no movement and produced a metallic sound in percussion. The tooth was consequently luxated and engaged again with a heavier force and followed-up monthly. Conclusion It re-erupted completely, and the follow-up periapical radiographs showed that root formation continued, and the root apex was approximately closed.